An Overuse Injury Leading to Pronator Teres Syndrome: A Case Report - Joel DeJonge; Sachin Singh; Denise Mourad; Lodewijk van Holsbeeck; Ihsan Al-Sabbagh (Annals of Internal Medicine: Clinical Cases)
Pronator teres syndrome (PTS) is a rare cause of compressive median nerve neuropathy in the proximal forearm, which often results from overuse. We present the case of a 25-year-old man who developed PTS due to work-related repetitive stress. Initially diagnosed with bursitis and carpal tunnel syndrome (CTS), investigation with electromyography and magnetic resonance imaging (MRI) confirmed PTS. Management with nonsteroidal anti-inflammatory drugs (NSAIDs), rest, and physical therapy led to significant symptom improvement. Our case highlights the importance of distinguishing PTS from other median nerve entrapment syndromes and emphasizes the utility of clinical and diagnostic evaluation in managing nerve compression.